MENYIBAK PEREMPUAN KEPALA KELUARGA - Ernawati, Ernawati (IAIN Pekalongan, 2013)
Abstract : This study departs from the reality of the increasing number of families are headed by women, but society and the government has not been paying attention and protection against them. This condition occurs because the patriarchal culture that assumes that women do not have the right to be the head of household. Standardization of gender roles, in which the male head of the household, the breadwinner and the wife is a housewife, dianggab be something natural, not a social construction that can and may at any time change, so it is very detrimental to women. Especially if the woman had to carry the load, to meet the economic needs of the whole family, as has happened in the lives of poor families. Abstrak : Penelitian ini berangkat dari realitas meningkatnya jumlah keluarga yang dikepalai oleh perempuan, tetapi masyarakat dan pemerintah belum memberikan perhatian dan perlindungan terhadap mereka. Kondisi ini terjadi karena budaya patriarki yang menganggap bahwa perempuan tidak memiliki hak untuk menjadi kepala rumah tangga. Standardisasi peran gender, di mana kepala laki-laki dari rumah tangga, pencari nafkah dan istri adalah ibu rumah tangga, dianggab menjadi sesuatu yang alami, bukan konstruksi sosial yang dapat dan dapat setiap perubahan waktu, sehingga sangat merugikan perempuan. Apalagi jika wanita harus membawa beban, untuk memenuhi kebutuhan ekonomi seluruh keluarga, seperti yang terjadi dalam kehidupan keluarga miskin